Examining the Relationship between Sex and Motivation in Triathletes. Issue 1 (August 2014) - López-Fernández, Iván; Merino-Marbán, Rafael; Fernández-Rodríguez, Emilio
The present paper assesses the relationship between sex and motivation in triathletes utilising a multidimensional measurement of motivation in sports. Data were collected from 138 triathlon participants (age range 17–72 years): 95 men ( M = 36.7yr., SD = 10.7) and 43 women ( M = 34.6yr., SD = 9.9). Measures included the Sport Motivation Scale, a multi-dimensional measure to assess different types of athletes' motivations for practising their sport. Results showed a significant sex difference in amotivation, with women displaying lower scores; but amotivation scores were very low. The results were not dependent on competition level or age. Men and women competing at the international level in triathlon have similar motivational profiles.